Tracking players in the game of handball - Pers, J.; Kovacic, S. (1999)
The early stage of the development of a tracking system for tracking players in indoor team games is presented. The development is focused on a non-invasive method of obtaining the player movement trajectories in the game of European or Team Handball. The trajectories can be further processed and analyzed by sports experts. As the non-invasive method is required, the visual tracking sistem, based on video representation of the specific match seems to be the optimal solution. The task of obtaining the trajectories consists of several processing stages. First, the raw video data is captured during the handball match using two video cameras mounted on the ceiling of the sports hall. The data is digitized, and videos are synchronized using the audio track of the video tape recorder. As the cameras are fitted with wide-angle lens, severe image distortion occurs, which has to be corrected at some stage of the process, along with the camera calibration. The digitized images from the video sequence are fed into the multiple-stage tracking module, which detects player movements by calculating the difference between current frame and the reference frame in the first stage, and employs different methods in the higher stages to ensure validity of the trajectory data. To simplify the tracker operation and ensure the validity of the results, players are manually marked by human operator on the first frame from the image sequence, and the tracker operation is monitored by human operator during the process. A voice interface between human operator and computer-based tracking system is considered.